(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2022)
In India, the most of the consumption is still at home. But with the time, convenience food consumption is increasing due to increase in urbanization , breaking up of the traditional joint family system, desire for quality ,shortage of time, increasing number of working women ,rise in percapita income, changing lifestyles and increasing level of affluence in the middle income group had brought about changes in food habits. The high speed and type constrained lifestyle of many consumers has forced to the rise of the convenience food industry and its significant influence on society’s food consumption behaviours. Consequently the food industry in India will face a rising demand for ready to cook food products. Ready to Cook foods can be defined as a food product which is beneficial to the consumer during any of the meal preparation and consumption stages: planning, storing, preparation, eating and disposal/tidy –up. This means a product which can be easily obtained, prepared, stored, served, or eaten, thus proving to be convenient by saving time, physical energy and mental energy.